Revealing 5 Core Character Education Values in Characterization of Circe in The Novel Circe by Madeline Miller - Cristiana, Olga; I Ketut Sudewa; Luh Putu Laksminy (Universitas Pendidikan Ganesha, 2025)
This study aimed to analyze the character education values in the Characterization of Circe in the Circe novel by Madeline Miller based on the 5 Core Values of the Ministry of Education and Culture (2017), namely religious, nationalist, independent, cooperative, and integrity. This study used a qualitative descriptive method with a textual analysis technique. Data were obtained through close reading and plot segmentation techniques to reveal the representation of the 5 core values contained in Circe's characterization. The results of the study showed that Circe represented the five values strongly: religious values were seen from Circe's recognition of divine power and her involvement in spiritual practices; independence values were reflected in Circe's independence in facing various challenges in her exile; cooperative values were seen in her cooperation with other characters in facing dangerous threats; and integrity values were seen in her honesty, life principles, and consistency of her actions. These findings indicate that the novel Circe can be used as reading material that can teach various good characters including the 5 core character education values through the characterization of the main character, Circe.